Pistacia Terebinthus Coffee Protects against Thioacetamide-Induced Liver Injury in Rats - Bahcecioglu, Ibrahim H.alil; Ispiroglu, Murat; Tuzcu, Mehmet; Orhan, Cemal; Ulas, Mustafa; Demirel, Ulvi; Şahin, Kazım (My University, 2015)
AIM/BACKGROUND: Pistacia terebinthus is used as a coffee substitute in the East and Southern Anatolia regions of Turkey. It contains unsaturated fatty acids, tocopherols, polyphenols and carotenoids. P. terebinthus has anti-inflammatory and potential antioxidant activity. In this study we evaluated the protective effects of P. terebinthus coffee (PTC) on thioacetamide (TAA)-induced liver injury in rats.; MATERIALS AND METHODS: Twenty-eight male Sprague-Dawley rats were equally randomized into four groups. Chronic liver injury was induced with TAA (100 mg/kg i.p. three times weekly). The first group of rats served as control and received only tap water (G1), and the remaining groups of rats received PTC, p.o (G2); TAA (G3); TAA plus PTC, p.o (G4), respectively.; RESULTS: After 8 weeks, PTC intake significantly reduced fibrosis/inflammation scores (p PTC intake reduced transforming growth factor beta (TGF-?) concentrations in the liver (p PTC intake.; DISCUSSION AND CONCLUSION: PTC intake provided beneficial effects against TAA-induced liver injury in rats. PTC probably suppresses the proinflammatory cytokines through NF-?B signaling pathway.
Keywords: Inflammation; Liver fibrosis; Liver injury; Pistacia terebinthus